An innovative echo detection system with STM32 gated and PMT adjustable gain for airborne LiDAR - Zhou, Guoqing; Li, Weihao; Zhou, Xiang; Tan, Yizhi; Lin, Gangchao; Li, Xianxing; Deng, Ronghua (International journal of remote sensing, 2021)
In bathymetric Airborne LiDAR (Light Detection And Ranging) for the measurement of various water depths, the echo of the laser signal is amplified by an amplifier circuit, the water surface is usually saturated, which results in a serious effect on the bottom echo signal. Therefore, this paper designs a LiDAR echo signal detection timing control system. The system adopts the STMicroelectronics32 (STM32) controller as the gated signal generator; acts on the photomultiplier tube (PMT) photoelectric conversion circuit; and adjusts the amplitude, frequency, period, and duty cycle of the gating trigger signal to achieve timing control, thus allowing the system to directly avoid the reception of overly strong surface echo signals and increasing the accuracy of the experimental results. The system combines PMT adjustable voltage control gain technology applies the weak underwater echo signal that is amplified to facilitate subsequent collection. In the actual measurement, using STM32 instead of the traditional signal generator, which can reduce the power consumption and load capacity of the system. The experimental results show that the system can amplify the underwater signal by at least 6-fold while avoiding the effect of the surface echo signal.